Tools and resources for preventing childhood obesity in primary care: A method of evaluation and preliminary assessment. Issue 5 (May 2016) - Avis, Jillian L.S.; Komarnicki, Angela; Farmer, Anna P.; Holt, Nicholas L.; Perez, Arnaldo; Spence, Nicholas; Ball, Geoff D.C.
Highlights: A mixed methods approach was piloted to evaluate tools for preventing obesity. Interviews with healthcare providers (HCPs) and assessment checklists were used. Most tools scored 'average' based on the checklists. Tools are multipurpose, and provider's use is impacted by logistical factors. Both objective scoring and input from HCPs can provide a more comprehensive evaluation of tools. Abstract: Objectives: To pilot-test a mixed methods approach to evaluate tools and resources (TRs) that healthcare providers (HCPs) use for preventing childhood obesity in primary care, and report a preliminary descriptive assessment of commonly-used TRs. Methods: This mixed methods study included individual, semi-structured interviews with purposefully-sampled HCPs in Alberta, Canada; interviews were digitally recorded and analyzed thematically (phase I). Two independent reviewers used three assessment checklists to evaluate commonly-used TRs (phase II). HCPs provided feedback on our coding scheme and checklist data (phase III). Results: Three themes described how HCPs ( n = 19) used TRs: purpose of use ( e.g ., clinical support), logistical factors ( e.g ., accessibility), and decision to use ( e.g ., suitability). The latter theme overlapped with constructs of suitability on the checklists. Overall, participants used 15 TRs, most of which scored 'average' on the checklists. Conclusion: Phases I and II provided unique insights on the evaluation of TRs used for preventing childhood obesity. Criteria on the checklists overlapped with HCPs' perceptions of TR suitability, but did not reflect logistical factors that influenced their use of TRs. Practice implications: Developers of TRs should collaborate with HCPs to ensure that subjective and objective criteria are used to optimize TR suitability in the primary care setting.